Effect of single and double pass friction stir processing on microhardness and wear properties of AA5083/Al2O3 surface composites. (2022) - Patel, Kevin; Ghetiya, Nilesh D.; Bharti, Shalok
Abstract: Friction Stir Processing (FSP) is an emerging technique for fabricating the surface composite of aluminium alloys. It consists of a rotating non-consumable tool due to which friction is generated between the workpiece surface and the tool. The basic principle of FSP is similar to that of the friction stir welding process (FSW). Most of the composite fabrication techniques change the bulk of material while with FSP only the surface properties of the workpiece alter while retaining the below surface properties same as that of the parent material. FSP helps to reduce the defects that are produced in the matrix alloy during the casting and also reduces distortion. Aluminium alloy AA5083 is known for its exceptional performance in extreme conditions. It highly resists attack by both water and industrial chemicals. It has also high tensile strength and shows high strength after welding so it is mostly used in shipbuilding, vehicle bodies, rail cars, and pressure vessels. In this paper, FSP was performed to produce the surface composites by using AA5083 as base matrix and Al2 O3 as reinforcement. Microstructure, Microhardness and wear characteristics of the prepared surface composites were measured and compared to the base material. The number of passes plays an important role during the FSP, therefore single pass and double pass FSP were applied in this study. Comparison between single pass and double passed surface composite showed that the double pass friction stir processed (FSPed) specimens give better microstructure, surface properties, and lesser defects than single-pass FSPed specimens. Double pass FSP gives better microstructure and better grain refinement in the prepared surface composite. Al2 O3 reinforcement was evenly distributed which provided enhanced microhardness. Results also show that the FSP specimens showed better wear resistance and coefficient of friction in comparison with the base alloy.